A Hermeneutic Analysis of Selected Yorùbá Pentecostal Songs - George Olusola Ajibade (Yoruba Studies Review)
The Christianity that reached Africa, especially the sub-Saharan region, had undergone several stages of inculturation and re-organization. The changing social, political, and cultural situation of the people had a tremendous impact on the Christian religion. As Christianity moved through the intellectual and political worlds, especially among the Yorùbá people of southwestern Nigeria, it acquired new categories of thought. Yorùbá philosophical language began to be applied in expressing some of the mysteries of the Christian faith. This was particularly evident in the articulation of the theological language expressed through various Christian songs. Different types of songs collected during the worship among the selected African Indigenous Churches and those produced by some artists were analyzed through the lens of textual exegesis. This paper considered the impact of the emerging trend of diffusion of African philosophy, worldviews, and Christian theology in the selected Christian songs. This in turn revealed the dynamism or the emerging trends in African Christianity that authenticate the pluricultural nature of contemporary world Christianity. The work demonstrated that Christianity is an essential part of the identity of the Yorùbá people, which is best demonstrated in the folkloric expressions, especially songs.